THE IMPLEMENTATION OF PHYSICAL AND HEALTH EDUCATION IN SCHOOL - Firdaus, Kamal - (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
Kamal Firdaus, December 2012. The Aplication Learning in General School. The problem of this paper is about the facilities, utilities, teachers quality and quantity, participation and extra work as well as the future is pledge of application of physical and healt education learning in general school. The aims of this paper are physical domain, psychomotor, cognittif and affectif. The conslusions of this paper are : Training program developing sports is a part of an effort in increasing physical and spintual of human a quality. The aim of physical education is oriented to the curriculum. The aplication of physical education in school is an effort of athletes talentskoting. Suggestions of this paper are: To keep balance between learning in one side and an effort of sport achievement increasing in another side. The quantity and the quality of teachers is the main support to the process of teaching and learning. There is the need inereasl the school facilities in quantity a well as the quality